2022
DOI: 10.1523/eneuro.0317-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

NPRL2 Inhibition of mTORC1 Controls Sodium Channel Expression and Brain Amino Acid Homeostasis

Abstract: Genetic mutations in nitrogen permease regulator-like 2 (NPRL2) are associated with a wide spectrum of familial focal epilepsies, autism, and sudden unexpected death of epileptics (SUDEP), but the mechanisms by which NPRL2 contributes to these effects are not well known. NPRL2 is a requisite subunit of the Gap Activity TOward Rags 1 (GATOR1) complex, which functions as a negative regulator of mammalian Target Of Rapamycin Complex 1 (mTORC1) kinase when intracellular amino acids are low.Here we show that loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
2
8
1
Order By: Relevance
“…Hoechst staining of brain slices revealed that mutant mice had significantly thicker cortices ( Figure 1 G), a consistent finding noted with mTORC1 upregulation ( Carson et al., 2012 ; Chen et al., 2019 ; Ishida et al., 2021 ; Yuskaitis et al., 2018 ). In addition to changes in size, mutant mice also demonstrated decreased survival, with no mutants surviving beyond 21 days of age which is similar to other studies ( Hui et al., 2022 ; Ishida et al., 2021 ) ( Figure 1 H), while heterozygotes displayed comparable survival to control littermates (data not included).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Hoechst staining of brain slices revealed that mutant mice had significantly thicker cortices ( Figure 1 G), a consistent finding noted with mTORC1 upregulation ( Carson et al., 2012 ; Chen et al., 2019 ; Ishida et al., 2021 ; Yuskaitis et al., 2018 ). In addition to changes in size, mutant mice also demonstrated decreased survival, with no mutants surviving beyond 21 days of age which is similar to other studies ( Hui et al., 2022 ; Ishida et al., 2021 ) ( Figure 1 H), while heterozygotes displayed comparable survival to control littermates (data not included).…”
Section: Resultssupporting
confidence: 89%
“…This increase in GFAP intensity is consistent with reactive astrogliosis as has been shown in multiple models of epilepsy ( Carson et al., 2012 ; Crowell et al., 2015 ) ( Figure S1 J). This astrogliosis occurs secondarily to neuronal Nprl2 loss, as pS6 staining was largely restricted to neurons and did not show any prominent overlap in expression with GFAP similar to other Nprl2 mouse models ( Hui et al., 2022 ; Ishida et al., 2021 ) ( Figures S1 J and S1K).…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations